Acetylcholinesterase loosens the brain's cholinergic anti-inflammatory response and promotes epileptogenesis - Gnatek, Yehudit; Zimmerman, Gabriel; Goll, Yael; Najami, Naim; Soreq, Hermona; Friedman, Alon (Frontiers in Molecular Neuroscience, 2012)
Recent studies show a key role of brain inflammation in epilepsy. However, the mechanisms controlling brain immune response are only partly understood. In the periphery, acetylcholine (ACh) release by the vagus nerve restrains inflammation by inhibiting the activation of leukocytes. Recent reports suggested a similar anti-inflammatory effect for ACh in the brain. Since brain cholinergic dysfunction are documented in epileptic animals, we explored changes in brain cholinergic gene expression and associated immune response during pilocarpine-induced epileptogenesis. Levels of acetylcholinesterase (AChE) and inflammatory markers were measured using real-time RT-PCR, in-situ hybridization and immunostaining in wild type (WT) and transgenic mice over-expressing the "synaptic" splice variant AChE-S (TgS). One month following pilocarpine, mice were video-monitored for spontaneous seizures. To test directly the effect of ACh on the brain's innate immune response, cytokines expression levels were measured in acute brain slices treated with cholinergic agents. We report a robust upregulation of AChE as early as 48 hrs following pilocarpine-induced status epilepticus (SE). AChE was expressed in hippocampal neurons, microglia and endothelial cells but rarely in astrocytes. TgS mice overexpressing AChE showed constitutive increased microglial activation, elevated levels of pro-inflammatory cytokines 48 hrs after SE and accelerated epileptogenesis compared to their WT counterparts. Finally we show a direct, muscarine-receptor dependant, nicotine-receptor independent anti-inflammatory effect of ACh in brain slices maintained ex vivo. Our work demonstrates for the first time, that ACh directly suppresses brain innate immune response and that AChE up-regulation after SE is associated with enhanced immune response, facilitating the epileptogenic process. Our results highlight the cholinergic system as a potential new target for the prevention of seizures and epilepsy.